The Scientific Values and its Behavioral Manifestations in the Biology Course for the Third Secondary Grade in the Kingdom of Saudi Arabia and methods of their inclusion in the course - Bukhari, Honorary Abdul Rahim (Journal of Educational and Psychological Sciences, 2021)
The study aimed to determine the extent of focus of biology course of third year of secondary school in the Kingdom of Saudi Arabia, for the year 1441 AH, on the scientific values and its behavioral manifestations, and to identify methods of including them in the course. A descriptive approach was used in analyzing the course content. A content analysis card was prepared to analyze the biology course content. The results of the study showed that the number of behavioral manifestations included in the ten scientific values in the study was (38) behavioral manifestations, and the total number of their occurrences in the course was (385). The five aspects that achieved the highest frequency in the biology course were: presentation of information (88), scientific honesty (62), deliberation in making judgments (60), scientific thinking (48), knowledge and love of knowledge (43). The results revealed that the biology course did not also focus at all on eleven behavioral aspects of scientific values. These aspects were: not neglecting other people’s criticisms, patience and restraint when facing frustrations, objectivity and avoiding bias in issuing judgments, taking into account the effects of scientific applications on society, avoiding myths, checking the truthfulness of data to reach accurate results, believing in the importance of science, realizing the link between religion and science, care for specialized reading, reverence and respect for scholars, and recognition of their role in the development of aspects of life, and originality in ideas. Among the results of the study, there was no clear methodological framework to enhance the scientific values ​​and their behavioral manifestations in the biology course for the third grade of secondary school. The implicit approach to the behavioral manifestations of the scientific value was topped in the biology course for the third high school, with total number of frequencies reached (242) with (63%). While the total number of occurrences of the explicit method of dealing with scientific values ​​was (143) with (37%). The method of explaining the paragraph was topped the methods of treating scientific values ​​in the biology course by (47%); followed by the method of treatment through evaluation activities, at a rate of (27%); in third place through objectives by (15%); and in the fourth place the method treated by visual regulator (1%).The study also made a number of recommendations to include scientific values ​​and their behavioral manifestations in the biology course for the third year of secondary school. Among the most prominent of them were: Promoting and enriching the content of the biology course for the with scientific values explicitly and not implicitly, and exerting more efforts in diversifying the methods of including the behavioral manifestations of those values in the course. Promoting scientific values in academic curricula in light of a scientific methodology, a specific and organized methodological framework, and clear and specific mechanisms. And training teachers on effective methods in teaching scientific values and their behavioral manifestations and enhancing them among students.